Names of soups in Kujawy dialects - Paluszak-Bronka, Anna (Papers in Linguistics, 2024)
The aim of the article is to present semantic and genetic description of Kujawy names of soups. This shall make it possible not only to explain the motivation and origin of the analyzed units, but also to demonstrate the diversity of dialects in Kujawy. Thanks to the knowledge of the analyzed names, it is also possible to recreate the culinary culture of the Kujawy countryside, which was characterized by self-sufficiency, consumption minimalism and seasonality.